Digital Light Processing Based Bioprinting with Composable Gradients. Issue 1 (23rd October 2021) - Wang, Mian; Li, Wanlu; Mille, Luis S.; Ching, Terry; Luo, Zeyu; Tang, Guosheng; Garciamendez, Carlos Ezio; Lesha, Ami; Hashimoto, Michinao; Zhang, Yu Shrike
Abstract: Recapitulation of complex tissues signifies a remarkable challenge and, to date, only a few approaches have emerged that can efficiently reconstruct necessary gradients in 3D constructs. This is true even though mimicry of these gradients is of great importance to establish the functionality of engineered tissues and devices. Here, a composable‐gradient Digital Light Processing (DLP)‐based (bio)printing system is developed, utilizing the unprecedented integration of a microfluidic mixer for the generation of either continual or discrete gradients of desired (bio)inks in real time. Notably, the precisely controlled gradients are composable on‐the‐fly by facilely by adjusting the (bio)ink flow ratios. In addition, this setup is designed in such a way that (bio)ink waste is minimized when exchanging the gradient (bio)inks, further enhancing this time‐ and (bio)ink‐saving strategy. Various planar and 3D structures exhibiting continual gradients of materials, of cell densities, of growth factor concentrations, of hydrogel stiffness, and of porosities in horizontal and/or vertical direction, are exemplified. The composable fabrication of multifunctional gradients strongly supports the potential of the unique bioprinting system in numerous biomedical applications. Abstract : A Digital Light Processing based (bio)printing system is developed, integrating a microfluidic mixer for the generation of composable gradients of desired (bio)inks on the fly. Various planar and volumetric structures exhibiting continual gradients of materials, cell densities, growth factor concentrations, hydrogel stiffness, and porosities in horizontal and/or vertical direction, are exemplified, suggesting the promising potential of the technology toward biomedical applications.